Proteomic organ-specific ageing signatures and 20-year risk of age-related diseases: the Whitehall II observational cohort study - Kivimäki, Mika; Frank, Philipp; Pentti, Jaana; Jokela, Markus; Nyberg, Solja T.; Blake, Acer; Lindbohm; Joni; V; Oh, Hamilton Se-Hwee; Singh-Manoux, Archana; Wyss-Coray, Tony; et al. (Elsevier BV, 2025)
Background
Biological ageing is known to vary among different organs within an individual, but the extent to which advanced ageing of specific organs increases the risk of age-related diseases in the same and other organs remains poorly understood.
Methods
In this observational cohort study, to assess the biological age of an individual's organs relative to those of same-aged peers, ie, organ age gaps, we collected plasma samples from 6235 middle-aged (age 45–69 years) participants of the Whitehall II prospective cohort study in London, UK, in 1997–99. Age gaps of nine organs were determined from plasma proteins via SomaScan (SomaLogic; Boulder, CO, USA) using the Python package organage. Following this assessment, we tracked participants for 20 years through linkage to national health records. Study outcomes were 45 individual age-related diseases and multimorbidity.
Findings
Over 123 712 person-years of observation (mean follow-up 19·8 years [SD 3·6]), after excluding baseline disease cases and adjusting for age, sex, ethnicity, and age gaps in organs other than the one under investigation, individuals with large organ age gaps showed an increased risk of 30 diseases. Six diseases were exclusively associated with accelerated ageing of their respective organ: liver failure (hazard ratio [HR] per SD increment in the organ age gap 2·13 [95% CI 1·41–3·22]), dilated cardiomyopathy (HR 1·65 [1·28–2·12]), chronic heart failure (HR 1·52 [1·40–1·65]), lung cancer (HR 1·29 [1·04–1·59]), agranulocytosis (HR 1·27 [1·07–1·51]), and lymphatic node metastasis (HR 1·23 [1·06–1·43]). 24 diseases were associated with more than one organ age gap or with organ age gaps not directly related to the disease location. Larger age gaps were also associated with elevated HRs of developing two or more diseases affecting different organs within the same individual (ie, multiorgan multimorbidity): 2·03 (1·51–2·74) for the arterial age gap, 1·78 (1·48–2·14) for the kidney age gap, 1·52 (1·38–1·68) for the heart age gap, 1·52 (1·12–2·06) for the brain age gap, 1·43 (1·16–1·78) for the pancreas age gap, 1·37 (1·17–1·61) for the lung age gap, 1·36 (1·26–1·46) for the immune system age gap, and 1·30 (1·18–1·42) for the liver age gap.
Interpretation
Advanced proteomic organ ageing is associated with the long-term risk of age-related diseases. In most cases, faster ageing of a specific organ increases susceptibility to morbidity affecting multiple organs.